Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1371/journal.pone.0186249
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of characteristic of human turbinate derived mesenchymal stem cells cultured in the serum free media

Abstract: We evaluated the effect of serum-free and xeno-cultivation (SFXFM) on the characterization, proliferation, and differentiation properties of human nasal stem cells (airway tissue; hTMSCs). hTMSCs were isolated from 10 patients, after which patient samples were separated into two groups, an SFXFM group and a control group. The control group was treated with bovine serum-containing medium. FACS analysis revealed that SFXFM-cultured hTMSCs maintained a characteristic mesenchymal stem cell phenotype. hTMSC prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…A high number of studies have well documented that human MSCs acquire cytogenetic alterations in culture both in autosomes and in sex chromosomes, even if they are frequently transient and not clonal [28,29,55,73,74,130,143,144,145,146,147,148,149,150,151,152,153]. Conversely, other studies reported stable chromosomes in culture for MSCs of different tissue origin [24,33,36,48,116,118,120,124,125,126,127,149,153,154,155,156,157,158]. Depending on the studies, tissue sources, culture conditions, culture times, these alterations occur at early or late passages and at different frequencies, thus explaining inconsistencies in literature data (for a detailed list of described aneuploidies, see Rebuzzini et al [148]).…”
Section: Genetic Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…A high number of studies have well documented that human MSCs acquire cytogenetic alterations in culture both in autosomes and in sex chromosomes, even if they are frequently transient and not clonal [28,29,55,73,74,130,143,144,145,146,147,148,149,150,151,152,153]. Conversely, other studies reported stable chromosomes in culture for MSCs of different tissue origin [24,33,36,48,116,118,120,124,125,126,127,149,153,154,155,156,157,158]. Depending on the studies, tissue sources, culture conditions, culture times, these alterations occur at early or late passages and at different frequencies, thus explaining inconsistencies in literature data (for a detailed list of described aneuploidies, see Rebuzzini et al [148]).…”
Section: Genetic Stabilitymentioning
confidence: 99%
“…Finally, culture conditions can greatly influence the biological properties of MSCs [50,118,154,158,174] including genomic stability [148]. Supplements seem to not influence genomic stability [36], whereas oxygen tension is critical [175] exerting a marked regulatory effect on cell cycle checkpoint genes [166]. It was demonstrated that long-term cultures under hypoxic conditions prevent senescence [82,83,84] while maintaining MSC differentiation potential.…”
Section: Genetic Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…For identity characterization, using gene expression assays such as Taqman TM to replace standard Tri-lineage differentiation staining assay is another example. While the current Tri-lineage differentiation assay requires 2–3 weeks for the cells to differentiate followed by staining and imaging ( Owston et al, 2019 ; Sanjurjo-Rodriguez et al, 2019 ; Rajpar and Barrett, 2020 ), newer methods such as the measurement of hMSC Tri-lineage gene expression following 1–2 weeks of differentiation reduces the time needed while providing quantitative information relative to the current method ( Szepesi et al, 2016 ; Hwang et al, 2017 ; Ling et al, 2020 ).…”
Section: Characterization and Safety Testing To Ensure Product Consistency Throughout The Manufacturing Workflowmentioning
confidence: 99%